Institutional support for High-tech manufacturing sectors - O. I. Dontsova; N. M. Abdikeev; V. M. Zotov (Управленческие науки, 2022)
Currently, a large-scale reform of the development institutions of the Russian Federation is planned and has begun to be implemented. The end result of the reform should be a fundamentally new ecosystem of investment support for technological growth processes. One of the important goals of a such ecosystem formation is to ensure the high competitiveness of the domestic world’s economy, as well as the compliance of the goals, strategies and policies of the development institutions in accordance with the Unifed Plan for achieving National Goals until 2030*. The authors of the paper concluded that today there were only general features of the reform of development institutions and were not defned such features as: future algorithms for institutions functioning, mechanisms of functioning, project selection mechanisms, project management mechanisms for monitoring the effectiveness of development institutions.